Let's Talk About Maths: The Role of Observed "Maths‐Talk" and Maths Provisions in Preschoolers' Numeracy. Issue 4 (25th October 2019) - von Spreckelsen, Megan; Dove, Emma; Coolen, Ilse; Mills, Annelot; Dowker, Ann; Sylva, Kathy; Ansari, Daniel; Merkley, Rebecca; Murphy, Victoria; Scerif, Gaia
ABSTRACT: Developmental cognitive neuroscience highlights the importance of interactions between children and their environment. As young children spend increasing time in childcare, it is key to investigate the impact of "maths‐talk" and maths provisions in preschools. Qualitative insights from early educators indicate a greater bias toward counting activities than would be expected given the Early Years curriculum. In addition, we quantified the observed breadth of preschool practitioners' maths language (e.g., place‐value language), setting‐based maths provisions (e.g., quality of maths‐related activities), and their relation with children's early numeracy skills. In settings with greater practitioners' breadth of maths language, children display greater cardinality skills although our data call for the further investigation of parental socioeconomic status and education. We conclude with a discussion on the need to operationalize children's maths learning environments as diversely as possible. Enriching practitioners' skill sets may be an effective and needed way of improving early maths outcomes.